Monotonicity-preserving doubly infinite matrices - Akgun, F. Aydin; Rhoades, B. E. (ELSEVIER SCIENCE INC, 2014)
We prove that a regular nonnegative doubly infinite matrix preserves all monotonicities of double sequences if and only if it is a conservative double Haudorff matrix with all nonnegative entries. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Monotonicity; Doubly infinite matrices; Doubly infinite Hausdorff matrices; Mathematics